Validation of 19-items wearing-off (WOQ-19) questionnaire to Portuguese - Carlos Eduardo MANTESE; Marcio MEDEIROS; Artur SCHUMACHER-SCHUH; Carlos Roberto de Melo RIEDER (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: The treatment of Parkinson disease with dopaminergic therapy improves functionality and quality of life. However, as the disease progresses, the wearing-off phenomenon develops. To improve the recognition of this phenomenon, the 19-item wearing-off questionnaire (WOQ-19) was developed. Objective: To translate and validate the WOQ-19 into Portuguese. Methods: The questionnaire was translated into Portuguese and, subsequently, back-translated into English and analyzed. The final version was tested in Parkinson disease patients for reliability through the test-retest paradigm and internal consistency. Also, sensitivity and specificity were obtained in different cut-off positive items. Results: The WOQ-19 showed good test stability, with an intraclass correlation coefficient of 0.877 (95%CI 0.690-0.951; p<0.001), and good internal consistency, with Cronbach alpha of 0.815. Two items of positive cut-off showed the best accuracy: 0.873 (95%CI 0.791-0.954). Sensitivity was 0.975 (95%CI 0.892-1) and specificity was 0.714 (95%CI 0.565-0.863). Conclusion: The Portuguese version of the WOQ-19 showed excellent diagnostic properties and can be used to diagnose wearing-off phenomena.